A Culture of Mattering: Building Staff Belonging, Purpose and Meaning at an Indigenous Recovery Centre - Downton, Mark J.; Biondi, Carolyn; Fulwiler, Dana; Curtis, Christy; Frederiksson, Evelina (2019)
The Ngwaagan Gamig Recovery Centre/Rainbow Lodge on the Wikwemikong Unceded Reserve in Ontario, Canada provides culturally-based alcohol and drug addiction treatment. We seek to support the staff’s sense of belonging and mattering, and engagement with their leader’s vision to incorporate positive psychology into the culture of the centre. Indigenous culture is being leveraged to heal from within after a history of oppression and cultural genocide in Canada (TRCC, 2015). Informed by the inherent resilience of the Anishinaabe people and culture, and current psychological science, we propose two positive interventions to cultivate mattering among staff. We recommend a peer support framework to establish a foundation of connection, and accompanying storytelling interventions grounded in Indigenous cultural practices. The literature emphasizes storytelling and cultural identity as essential for building resilience and belonging in Indigenous communities, especially for those dealing with addiction. We build upon current storytelling initiatives at Rainbow Lodge and incorporate Anishinaabe culture. We suggest culturally relevant measurement through talking circles and tools already used by the Rainbow Lodge to measure impact. We believe the proposed applications will enhance among the staff a sense of individual and community belonging, purpose and mattering, resulting in a willingness to participate and contribute to new initiatives, and overall increased well-being.